URGENSI KRIMINALISASI TERHADAP ANAK PELAKU HOMOSEKSUAL DALAM PEMBAHARUAN HUKUM PIDANA INDONESIA - Lamtiur Siregar; Erdianto Effendi; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Homosexual or same-sex sex, now is not a new thing in Indonesia.The reality of the existence of homosexuals knows no age restrictions;profession; and social and religious status. Criminalization efforts throughJudicial Review are only aimed at people with certain sexual orientation,such as LGBT or Lesbian people; Gay; Bisexual; Transgender. If you lookfurther, the Judicial Review or test material submitted by the applicant isaimed at all people regardless of their sexual orientation, both those whohave homosexual or heterosexual orientation.This type of research is normative legal research, because in variouscases the issue that is rife among Indonesian people. Children asperpetrators of same-sex acts between men and men (Gay) or women andwomen (lesbians) and even the nature of this research is descriptive, thisstudy provides an overview of the main problems namely homosexuality inthe renewal of Indonesian criminal law.From the results of this study that it is very important to do theUrgency of criminalization for children as homosexuals who should bechildren as the successor of the nation. Criminalization aims to createlegal certainty for the protection and welfare of the community, so it isvery important to do the rules in terms of actions that can be accounted foreven if the child cannot be sanctioned, the author is very enthusiastic insupporting this paper so that the rules of behavior of the child as an actorare carried out homosexuals in Indonesian society.Keywords: urgency, child homosexuals, criminalization